A Dual Interaction Between the 5′- and 3′-Ends of the Melon Necrotic Spot Virus (MNSV) RNA Genome Is Required for Efficient Cap-Independent Translation - Miras, Manuel; Rodríguez-Hernández, Ana M.; Romero-López, Cristina; Berzal-Herranz, Alfredo; Colchero, Jaime; Aranda, Miguel A.; Truniger, Verónica (Frontiers in Plant Science, 2018)
In eukaryotes, the formation of a 5´-cap and 3´-poly(A) dependent protein-protein bridge is required for translation of its mRNAs. In contrast, several plant virus RNA genomes lack both of these mRNA features, but instead have a 3´-CITE (for cap-independent translation enhancer), a RNA element present in their 3´-untranslated region that recruits translation initiation factors and is able to control its cap-independent translation. For several 3´-CITEs, direct RNA-RNA long-distance interactions based on sequence complementarity between the 5´- and 3´-ends are required for efficient translation, as they bring the translation initiation factors bound to the 3´-CITE to the 5´-end. For the carmovirus melon necrotic spot virus (MNSV), a 3´-CITE has been identified, and the presence of its 5´-end in cis has been shown to be required for its activity. Here, we analyze the secondary structure of the 5´-end of the MNSV RNA genome and identify two highly conserved nucleotide sequence stretches that are complementary to the apical loop of its 3´-CITE. In in vivo cap-independent translation assays with mutant constructs, by disrupting and restoring sequence complementarity, we show that the interaction between the 3´-CITE and at least one complementary sequence in the 5´-end is essential for virus RNA translation, although efficient virus translation and multiplication requires both connections. The complementary sequence stretches are invariant in all MNSV isolates, suggesting that the dual 5´-3´ RNA:RNA interactions are required for optimal MNSV cap-independent translation and multiplication.